2015
DOI: 10.1016/j.parkreldis.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of cognitive domains with postural instability/gait disturbance in Parkinson's disease

Abstract: Introduction Research suggests an association between global cognition and postural instability/gait disturbance (PIGD) in Parkinson’s disease (PD), but the relationship between specific cognitive domains and PIGD symptoms is not clear. This study examined the association of cognition (global and specific cognitive domains) with PIGD symptoms in a large, well-characterized sample of individuals with PD. Methods Cognitive function was measured with a detailed neuropsychological assessment, including global co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
71
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 29 publications
11
71
0
4
Order By: Relevance
“…This is in keeping with recent findings showing impaired postural control in FoG+ compared to FoG− [16]. We hypothesized that sway dispersion or smoothness would be affected by dual task since executive and memory functions have been found to be related to postural instability assessed by the PIGD subscore [24]. However, although we found differences between groups in PIGD and in the MiniBESTest, we did not see a dual-task interference during postural sway in FoG+ compared to FoG−, which may be explained by the fact that both groups were cognitively intact, as the MoCA scores were similar.…”
Section: Discussionsupporting
confidence: 83%
“…This is in keeping with recent findings showing impaired postural control in FoG+ compared to FoG− [16]. We hypothesized that sway dispersion or smoothness would be affected by dual task since executive and memory functions have been found to be related to postural instability assessed by the PIGD subscore [24]. However, although we found differences between groups in PIGD and in the MiniBESTest, we did not see a dual-task interference during postural sway in FoG+ compared to FoG−, which may be explained by the fact that both groups were cognitively intact, as the MoCA scores were similar.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are in line with these concepts. Indeed, our observation of significant improvements in motor and cognitive performances after four weeks of treadmill training in the Intervention group provides further confirmation of the close relationship between impaired cognitive performance and motor dysfunction in patients with PD (Varalta et al, 2015;Kelly et al, 2015). These findings have relevance to rehabilitation, considering that PDassociated cognitive deficits are important features of the disease, contributing to reduced quality of life and an increased risk of disability and mortality (Kelly et al, 2015).…”
Section: Discussionsupporting
confidence: 69%
“…This finding is consistent with findings from a recent study of patients with PD that showed that after adjusting for non-PIGD items on the MDS-UPDRS III, a higher PIGD score was associated with more severe deficits in global cognition, executive function, memory, and phonemic fluency. 22 …”
Section: Discussionmentioning
confidence: 99%